Non alcoholic fatty liver disease increases the mortality from acute coronary syndrome; an observational study from Sri Lanka - Perera, N.; Indrakumar, J.; Abeysinghe, W.V.; Fernando, V.; Samaraweera, W.M.C.K.; Lawrence, J.S. (BMC Cardiovascular Disorders, 2016)
Attached

Background: Non alcoholic fatty liver disease is an independent risk factor for coronary artery disease. But its effect on acute coronary syndrome is not clear. We performed this study to identify the prevalence of NAFLD in patients with ACS admitted to a tertiary care center in Sri Lanka. We also described the association of NAFLD with the severity of ACS predicted by the GRACE score. Methods: We performed a descriptive study including all consecutive patients with non-fatal ACS admitted to Colombo South Teaching Hospital from 01/02/2014 to 30/04/2014. Patients with excessive alcohol consumption, established cirrhosis and patients with identified risk factors for liver disease were excluded from the study. All patients underwent ultrasound scan of liver. Results: There were 120 participants, 75 (62.5 %) males and 45 (37.5 %) females with acute coronary syndrome. Average age was 61.28 ± 11.83 years. NAFLD was seen in 56 (46.7 %) patients with ACS. Patients with NAFLD had a higher GRACE score than patients without NAFLD (120.2 ± 26.9 Vs 92.3 ± 24.2, p < 0.001). Increased age and presence of NAFLD conferred a higher mortality risk from ACS as predicted by GRACE score. Patients with NAFLD had a higher predicted mortality during in-ward stay (adjusted OR 31.3, Cl 2.2-439.8, p = 0.011) and at 6 months after discharge (adjusted OR 15.59, 0 1.6-130.6, p = 0.011). Conclusions: Patients with NAFLD have a higher predicted mortality from acute coronary syndrome and thus require aggressive treatment of CAD. It is important to consider this novel risk factor when risk stratifying patients with ACS.
Keywords: Non alcoholic fatty liver disease; Acute coronary syndrome; Mortality; Sri Lanka